Normal foetal kidney volume in offspring of women treated for gestational diabetes. Issue 4 (30th August 2019) - Hokke, Stacey; de Zoysa, Natasha; Carr, Bethany L.; Abruzzo, Veronica; Coombs, Peter R.; Allan, Carolyn A.; East, Christine; Ingelfinger, Julie R.; Puelles, Victor G.; Black, Mary J.; Ryan, Danica; Armitage, James A.; et al.
Abstract: Aims: The worldwide prevalence of gestational diabetes mellitus (GDM) is increasing. Studies in rodent models indicate that hyperglycaemia during pregnancy alters kidney development, yet few studies have examined if this is so in humans. The objective of this study was to evaluate the association of treated GDM with foetal kidney size. Materials and Methods: Participants were recruited from an Australian tertiary hospital, and clinical data were collected from women without GDM and women diagnosed and treated for GDM and their offspring. Participants underwent an obstetric ultrasound at 32‐34 weeks gestation for foetal biometry and foetal kidney volume measurement. Results: Sixty‐four non‐GDM and 64 GDM women participated in the study. Thirty percent of GDM women were diagnosed with fasting hyperglycaemia, while 89% had an elevated 2‐hour glucose level. Maternal age, weight and body mass index were similar in women with and without GDM. Estimated foetal weight, foetal kidney dimensions, total foetal kidney volume and birth weight were similar in offspring of women with and without GDM. Conclusions: We conclude that a period of mild hyperglycaemia prior to diagnosis of GDM and treatment initiation, which coincides with a period of rapid nephron formation and kidney growth, does not alter kidney size at 32‐34 weeks gestation. Abstract : The aim of this prospective cohort study was to evaluate the effect of GDM on foetal kidney size in women attending an Australian tertiary hospital. Our findings suggest that foetal kidney size is normal in offspring of women diagnosed and treated for GDM.